Classification, Diagnosis and Treatment of Sinusitis: Evidence-Based Clinical Practice Guidelines - Arnold Noyek; David Brodovsky; Stephen Coyle; Martin Desrosiers; Saul Frenkiel; Michael Hawke; James D Kellner; David A Kirkpatrick; Sigmund Krajden; Donald E Low; Lionel Mandell; Bernard Marlow; et al. (Canadian Journal of Infectious Diseases)
OBJECTIVE: To provide evidence-based recommendations for classification, diagnosis and treatment of acute, chronic and recurrent acute sinusitis in adults and children.